Lie detection: A strategic analysis of the Verifiability Approach - Konstantinos Ioannidis; Theo Offerman; Randolph Sloof (Tinbergen Institute, 2020)
The Verifiability Approach is a lie detection method based on the insight that truth-tellers provide precise details whereas liars sometimes remain vague to avoid being exposed. We provide a-game-theoretic analysis of a speaker who wants to be acquitted and an investigator who prefers to find out the truth. The investigator can verify the speakerâ exteuro™s statement at some cost; verification gets more reliable the more details are provided. If, after a falsified statement, the investigator convicts, an additional obstruction penalty is imposed. We derive all the equilibria of the game and thereby the conditions under which the investigator can infer additional information from the speaker's statement at face value. Strategic information revelation by the speaker and verification by the investigator then necessarily work in tandem. Improvements in reliability result in more valuable (strategic) information transmission, whereas a harsher obstruction penalty does not as soon as a lower limit is met.
Keywords: K14; C72; D01; D82; 330; Lie detection; Verifiability approach; Strategic information revelation